Placement and compaction of asphalt mixtures : a symposium - Wagner, F. T.; ASTM. Committee D-4 on Road and Paving Materials (Philadelphia, Pa. (1916 Race St., Philadelphia 19103) : American Society for Testing and Materials)
Includes bibliographies and index.